Spontaneous locomotor activity and L-DOPA-induced dyskinesia are not linked in 6-OHDA parkinsonian rats - Sgroi, Stefania; Kaelin-Lang, Alain; Capper-Loup, Christine (Frontiers in Behavioral Neuroscience, 2014)
Bradykinesia (slowness of movement) and other characteristic motor manifestations of Parkinson’s disease (PD) are alleviated by treatment with L-dihydroxyphenylalanine (L-DOPA). Long-term L-DOPA treatment, however, is associated with complications such as motor fluctuations and dyskinesia that severely impair the quality of life. It is unclear whether the effect of L-DOPA on spontaneous motor activity and its dyskinesia-inducing effect share a common mechanism. To investigate the possible connection between these two effects, we analyzed the spontaneous locomotor activity of parkinsonian rats before surgery (unilateral injection of 6-OHDA in the right medial forebrain bundle), before treatment with L-DOPA, during L-DOPA treatment (the “ON” phase), and after the end of L-DOPA treatment (the “OFF” phase). We correlated the severity of dyskinesia (AIM scores) with locomotor responses in the ON/OFF phases of chronic L-DOPA treatment at two different doses. We treated three groups of parkinsonian animals with chronic injections of 8 mg/kg L-DOPA, 6 mg/kg L-DOPA, and saline solution and one group of non-lesioned animals with 8 mg/kg L-DOPA. At the end of the experiment, tyrosine hydroxylase (TH) immunoreactivity was analyzed in the striatum of all parkinsonian rats. We found no correlation between the severity of dyskinesia and spontaneous locomotor activity in the ON or OFF phase of L-DOPA treatment. The only observed correlation was between the pathological rotation induced by L-DOPA at the highest dose and locomotor activity in the ON phase of L-DOPA treatment. In addition, a L-DOPA withdrawal effect was observed, with worse motor performance in the OFF phase than before the start of L-DOPA treatment. These findings suggest that different neural mechanisms underlie the effect of L-DOPA on spontaneous motor activity and its dyskinesia-inducing effect, with a different dose-response relationship for each of these two effects.